ANALISIS HUBUNGAN KEKERABATAN JAMBU AIR (Syzigium aqueum (Burm.f.). Alston) DI KOTA PEKANBARU DAN KABUPATEN KAMPAR BERDASARKAN KARAKTER MORFOLOGI - Nanda Marlian Iriani; Nery Sofiyanti; Fitmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Water apple is one of agricultural commodities in Indonesia, including Riau Province. In this Province, this species is mainly distributed in Pekanbaru and Kampar. The diversity of water apple in both regions is high, however, there is no record of its morphological diversity study. This study aimed to identify and to know the diversity of water apple from Pekanbaru and Kampar based on the morphological characters. This research had been carried out from April 2013 to January 2014 using survey and observation methods. The morphological characters were observed and described. The scoring of morphological characters was then analyzed using NTSYS-pc 2.02i. The numbers of variation found in tree, leaf, flower, fruit and seed were 4, 5, 7, 9 and 3 respectively. The similarity coefficient ranged from 0.16 to 0.77. The highest similarity was found on individual R8 and R7, while the lowest similarity coefficient was found on individual KM10 and BR8. Result of cluster analysis showed that the relationship of water apples ranged from 0.41 to 0.78.